Perlindungan Hukum Keselamatan Kerja di PT Pertamina RU III Plaju dalam Proyek Kilang Minyak - Nugraha, Abyan; Wardhana, Arief Wisnu; Kasra, Helwan; Mahfuz, Abdul Latif (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this article is to examine legal protection for the safety of PT Pertamina Refinery Unit III Plaju workers in the oil refinery project agreement and the legal consequences of termination of employment. The method is normative with secondary data as the main source. The results show that worker safety protection is in accordance with the law, including the provision of protective equipment such as protective clothing, safety shoes and head protection. However, its implementation is not optimal because many workers are not aware of the importance of safety. If employment is terminated, workers are entitled to compensation in accordance with article 165 of the Employment Law. They get severance pay, long service awards and other rights with a certain nominal value. Workers are also considered creditors whose payments take precedence, giving them a priority position in claims.